Imidazolium-based titanium substrates against bacterial colonization. (31st January 2017) - Cavoue, T.; Bounou Abassi, H.; Vayssade, M.; Nguyen Van Nhien, A.; Kang, I.-K.; Kwon, G.-W.; Pourceau, G.; Dubot, P.; Abbad Andaloussi, S.; Versace, D.-L.
Abstract : Photografting of a silane-derived imidazole compound on titanium substrates against bacterial colonization. Abstract : Nosocomial infections are often induced by the presence of pathogenic organisms on the surface of medical devices or hospital equipment. Chemical modifications of the surface are recognized as efficient strategies to prevent bacterial adhesion but they may have a negative impact on the material's interaction with living tissues. Here we have developed a photoactivated method for the modification of titanium substrates. A photoinduced technique employing a grafting-onto process has been successfully performed to covalently anchor an imidazolium-derivative siloxane onto titanium surfaces. Imidazolium surfaces showed higher bacteria-repellency performances than native titanium substrates, achieving more than 98% anti-adhesion efficiency against Escherichia coli after 24 h of incubation. In addition, these surfaces allowed for the adhesion and viability of osteoblasts cells without evidence of cytotoxicity.